Nocturnal periodicity of Phlebotomus (Larroussius) orientalis (Diptera: Psychodidae) in an endemic focus of visceral leishmaniasis in Northern Ethiopia - Gebresilassie, Araya (Parasit Vectors, 2015)
BACKGROUND: Phlebotomus orientalis is the major vector of the intramacrophage protozoa, Leishmania donovani, the etiological agent of visceral leishmaniasis (VL) in northern Ethiopia and Sudan. The objective of this study was to determine the nocturnal periodicity of P. orientalis in the VL endemic focus of Tahtay Adiyabo district, northern Ethiopia. METHODS: Sandflies were collected using CDC light traps by changing collecting bags at an hourly interval from dusk to dawn for six months (January-June 2013) from outdoors (i.e. peri-domestic and agricultural fields). Sandfly specimens collected in the study were identified to species level and counted. RESULTS: In total, 21,716 nocturnally active sandfly specimens, which belong to two genera (i.e., Phlebotomus and Sergentomyia) were collected and identified. In the collection, P. orientalis, the dominant species in the genus Phlebotomus, constituted 33.79% while Sergentomyia spp. comprised 65.44%. Analysis of data showed that activity of P. orientalis females increased from 18:00 to 24:00 hours, with a peak after midnight (24:00–03:00 hrs). Likewise, activity of parous P. orientalis females was found to be unimodal, peaking at 24–01:00 hrs. CONCLUSION: P. orientalis females had marked nocturnal activity, which peak after midnight. Similarly, the epidemiologically dangerous parous females generally were more active after midnight. Therefore, humans are at risk of L. donovani infections through the bite of P. orientalis possibly between midnight and dawn.